Procurement institutions and essential drug supply in low and middle-income countries - Nahim Bin Zahur; Lucy Xiaolu Wang (Queen's University, Department of Economics, 2024)
International procurement institutions play an important role in drug supply. We study price, delivery, and procurement lead time of drugs for major infectious diseases (antiretrovirals, antimalarials, antituberculosis, and antibiotics) in 106 developing countries from 2007-2017 across procurement institution types. We find that pooled procurement lowers prices: pooling internationally is most effective for small buyers and concentrated markets, while pooling within-country is most effective for large buyers and unconcentrated markets. Pooling can reduce delays, but at the cost of longer anticipated lead times. Finally, pooled procurement is more effective for older-generation drugs, compared to patent pooling institutions that target newer drugs.
Keywords: I11; O19; H57; 330; global drug diffusion; procurement institutions; price and delay; IP and non-IP barriers